1989
DOI: 10.1002/1097-0142(19890301)63:5<839::aid-cncr2820630508>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell carcinoma in high-grade high-stage ovarian carcinoma. An indicator of favorable response to chemotherapy

Abstract: We reviewed 53 high-grade carcinomas of the ovary in order to define pathologic features that correlate with prognosis. All tumors were Stage III with comparable amounts of residual tumor left after the primary resection. Similar postoperative chemotherapeutic regimens were given to each patient, and there was a clinical followup of at least four years in each case. The tumors were classified according to their predominant (greater than 50%) histology as transitional cell carcinoma (TCC) (18 tumors), papillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“…There is controversy about the significance of transitional cell pattern in ovarian carcinoma, and it has been suggested that this pattern is associated with a more favorable response to chemotherapy compared to usual HGSC; however, these findings have not been consistent, which is not surprising given the lack of reproducible diagnostic criteria, so that different case series undoubtedly have significant differences in case composition [81,[87][88][89][90][91]. It is possible that this pattern of growth is associated with improved resectability and response to chemotherapy, but the absence of reproducible diagnostic criteria or useful molecular markers makes definitive studies impossible at this time.…”
Section: Treatmentmentioning
confidence: 99%
“…There is controversy about the significance of transitional cell pattern in ovarian carcinoma, and it has been suggested that this pattern is associated with a more favorable response to chemotherapy compared to usual HGSC; however, these findings have not been consistent, which is not surprising given the lack of reproducible diagnostic criteria, so that different case series undoubtedly have significant differences in case composition [81,[87][88][89][90][91]. It is possible that this pattern of growth is associated with improved resectability and response to chemotherapy, but the absence of reproducible diagnostic criteria or useful molecular markers makes definitive studies impossible at this time.…”
Section: Treatmentmentioning
confidence: 99%
“…When these neoplasms are well sampled, they often contain foci of classic serous or endometrioid adenocarcinoma 83. There is some weak evidence that transitional carcinomas may be more chemoresponsive than other primary ovarian carcinomas 2 87. There has been little or no study of the underlying molecular events in ovarian transitional carcinoma.…”
Section: Transitional Carcinomamentioning
confidence: 99%
“…These are uncommon tumors; Silva et al estimated that they account for 1% of ovarian carcinomas (52). Transitional cell carcinomas may show a more favorable response to chemotherapy than other ovarian carcinomas, but this has not been a uniform finding (3,(52)(53)(54)(55)(56). With a recently recognized tumor subtype there will be problems with reproducibility in diagnosis.…”
Section: Transitional Cell Carcinomasmentioning
confidence: 99%